Democratic Misalliances. - Ross, Benjamin (Dissent (0012-3846))
Discusses the alliances of Democratic Leadership Council of the U.S. and strategies adopted by it to win votes. Measures taken by New Democrats to draw votes from upscale suburban constituency including favor for gay rights and raising abortion issue; Approach of gun control followed by New Democrats to retain votes of Blacks; Maintenance of Democratic support by relying on Republican racism and xenophobia by democrats.